Incubación artificial de huevos embrionados de Tilapia Roja Oreochromis sp (2002)
ABSTRACT: The major problems of traditional mass seed production in mouthbrooding tilapias are: Low egg production per spawning, high spawning frequency, early sexual maturing, low fecundity and the high investment in parental care, obtaining fry of differtent size. Collecting the eggs or the fry from the oral cavity of mouthbrooding females reared in large hapas suspended in fertilized ponds to continue the incubation artificially, has been found to be possible and commercially efficient. Another critical aspect for industrial purposes in culturing tilapia is the hormone treatment for sex reversion, since the spawn is not synchronized among the females. This leads to sex mixture, to undesirable reproduction in the growth pond, to different age groups and sizes, and to delayed harvest. The goal of this article is to describe the artificial incubation system of the tilapia eggs like tool to resolve this difficulty.